Use of Antibiotic Eluting Calcium Sulfate Beads in High-Risk Primary Total Knee Arthroplasty - Su, Lisa; Park, Jeannie; Mao, Yifan; Wong, Murray; Dipane, Matthew V.; Sassoon, Adam (The Journal of Knee Surgery, 2025)
Local delivery of high-dose antibiotics via absorbable calcium sulfate beads has been investigated as a treatment of prosthetic joint infection (PJI). We investigate this strategy as a prophylactic measure for high-risk patients undergoing primary total knee arthroplasty (TKA). A retrospective review of a single-surgeon consecutive series of primary TKA patients with identified risk factors for PJI development was performed. These patients were treated with calcium sulfate beads containing 1 g of vancomycin and 1.2 g of tobramycin per 10 cc, with 10 cc placed intraarticularly. Outcomes included PJI, wound complications, revision surgery, and medical complications. There were 114 knees in 103 patients, with 76 women (66.7%), a mean age of 66.8 years (range: 21–91), and a mean follow-up of 16 months (range: 3–55). The mean preoperative lifetime PJI risk based on the 2018 International Consensus Meeting on the PJI calculator was 11.3% (standard deviation: 16.3%, range: 0.9–94.3%). Risk factors included medical comorbidities, homelessness, chronic urinary tract infection, other PJI or septic arthritis history, or prior ipsilateral knee surgeries. One delayed PJI occurred 1 year postoperatively from presumed hematogenous seeding following dialysis. There were no other known deep infections. There were nine patients who had delayed wound healing with marginal skin necrosis—six resolved with wound care and three underwent superficial extraarticular surgical debridement. There was one patient who underwent aseptic revision for patellar instability and nine patients required manipulation under anesthesia for stiffness. There was one patient who died after readmission for cardiac arrhythmia and one patient had bilateral DVT. No cases of chronic PJI, persistent wound drainage, or postoperative hypercalcemia were identified. Prophylactic use of antibiotic-eluting calcium sulfate beads in primary TKA has resulted in low rates of early PJI in a high-risk cohort, warranting further prospective studies and investigation.
Keywords: knee; periprosthetic joint infection; infection; prevention; prophylaxis; antibiotic beads